Analysis of the journalistic coverages of La Crónica, El Comercio and Depor newspaper during the participations of Peru in 1939, 1975 and 2019 Copa America - Gozzing Takuda, César Alexis (2021)
The written press has undergone many changes, both in its physical format and in the construction of the texts. Over the years, written sports journalism began to mix information with spectacularity to report on the participation of the national soccer team. For this reason, the motivation arises to know the journalistic coverage that the newspapers provided to the participation of Peruvians in large-scale competitions. The objective of this research is to analyze the characteristics or qualities of the news from the newspapers La Crónica from 1939, El Comercio from 1975 and Depor from 2019, with respect to the performance of the peruvian soccer team in the finals of the Copa América. The type of research is applied at a descriptive comparative level. The notes chosen are those drawn up the day after the matches played. The population is 31 notes and the sample is 11 notes. Regarding the content, a style according to the norms and customs of each era is observed in the three newspapers; in addition, the playful approach is appreciated over the information, but without losing the informational essence.